Growth, toxin production, active oxygen species and catalase activity of Microcystis aeruginosa (Cyanophyceae) exposed to temperature stress - Giannuzzi, Leda (2016)
Microcystis are known for their potential ability to synthesize toxins, mainly microcystins (MCs). In order to evaluate the effects of temperature on chlorophyll a (Chl a), growth, physiological responses and toxin production of a native Microcystis aeruginosa, we exposed the cells to low (23 °C) and high (29 °C) temperature in addition to a 26 °C control treatment. Exponential growth rate was significantly higher at 29 °C compared to 23 °C and control, reaching 0.43, 0.32 and 0.33 day−1 respectively. In addition, there was a delay of the start of exponential growth at 23 °C. However, the intracellular concentration of Chl a decreased significantly due to temperature change. A significant increase in intracellular ROS was observed in coincidence with the activation of enzymatic antioxidant catalase (CAT) during the first two days of exposure to 23° and 29 °C in comparison to the control experiment, decreasing thereafter to nearly initial values. Five MCs were determined by LC-MS/MS analysis. In the experiments, the highest MC concentration, 205 fg [Leu1] MC-LR.cell− 1 expressed as MC-LR equivalent was measured in the beginning of the experiment and subsequently declined to 160 fg.cell− 1 on day 2 and 70 fg.cell− 1 on day 4 in cells exposed to 29 °C. The same trend was observed for all other MCs except for the least abundant MC-LR which showed a continuous increase during exposure time. Our results suggest a high ability of M. aeruginosa to perceive ROS and to rapidly initiate antioxidant defenses with a differential response on MC production.